Parody in English Literature. The Case of Edward Bond's Lear. A Stylistic Study. - Kordi Nihed Nour El Houda; Mehellou Soukaina (University of El-Oued جامعة الوادي, 2025)
ملخص: تبحث هذه الدراسة في طبيعة ووظيفة المحاكاة الساخرة في الأدب عمومًا. كدراسة حالة، يُتبع تحليل المحاكاة الساخرة، كأداة أسلوبية وموضوعية، في مسرحية إدوارد بوند "لير"، وهي إعادة تفسير حديثة لمسرحية الملك لير لشكسبير. يسعى البحث إلى استكشاف كيفية عمل المحاكاة الساخرة، متجاوزًا التقليد أو الهجاء البسيط، ليُصبح أداة فعّالة للنقد الاجتماعي والسياسي. بالإضافة إلى ذلك، تُعيّن الدراسة مناهج نوعية وأسلوبية للتحقيق في كيفية إعادة بوند تفسير النص الأصلي من خلال استراتيجيات لغوية وسردية ونظرية تداخل النصوص. فبدلاً من استخدام المحاكاة الساخرة للفكاهة فقط، يستخدمها بوند كعملية نقد اجتماعي وسياسي، كاشفًا عن قضايا الاستبداد والعنف والانحلال الأخلاقي في المجتمع الحديث. من الناحية الأسلوبية، ينحرف بوند عن عظمة شكسبير الشعرية من خلال لغة مجزأة ومباشرة، وغالبًا ما تكون وحشية. يعكس رفضه للجماليات التقليدية تشككًا ما بعد حداثي تجاه الأشكال الأدبية الموروثة. يُعتبر إدوارد بوند شخصية مثيرة للجدل في المسرح الحديث نظرًا لتصويره الصريح للعنف وإيمانه بأن الفن يجب أن يؤدي وظائف أخلاقية وسياسية. ينظر بوند إلى المسرح كقوة أخلاقية، ووسيلة لكشف وتحدي هياكل السلطة بدلًا من مجرد الترفيه. من خلال تحليل أساليب بوند الدرامية ولغته، توضح الدراسة كيف تتحدى المحاكاة الساخرة في مسرحية "لير" المعايير الأدبية التقليدية، وتعكس السلطة والعدالة والعلاقات الأسرية. تؤكد النتائج على أهمية المحاكاة الساخرة كتقنية أدبية تحويلية في الأدب، قادرة على إعادة صياغة السرديات الكلاسيكية لمعالجة القضايا الثقافية والسياسية المعاصرة. Abstract This study investigates the nature and function of parody in literature in general. As a case study, an analysis of parody, as a stylistic and thematic tool, is followed in Edward Bond’s Lear, a modern reinterpretation of Shakespeare’s King Lear. The research pursues to explore how parody works beyond simple imitation or satire, serving instead as an effective device for socio-political critique. In addition, the study appoints qualitative and stylistic approaches to investigate how Bond reinterprets the original text through linguistic, narrative strategies and intertextual theory. Instead of utilizing parody only for humor, Bond employs it as a process of socio-political critique, detecting the issues of authoritarianism, violence, and ethical dissolution in modern society. Stylistically, Bond diverges from Shakespeare’s poetic grandeur through a fragmented, direct, and often brutal language. His rejection of traditional aesthetics reflects a postmodern skepticism toward inherited literary forms. Edward Bond is considered as a controversial figure in modern theatre due to his explicit portrayal of violence and his belief that art must fulfill ethical and political functions. Bond views theatre as a moral force—a means to expose and challenge power structures instead of merely entertain. By analyzing Bond’s dramatic methods and language, the study illustrates how parody in Lear confronts conventional literary norms and mirrors on power, justice, and familial relationships. The findings emphasize the importance of parody as a transformative literary technique in literature, able to re-contextualize classic narratives to address contemporary cultural and political concerns.
Master's Degree In Literature and Civilization. 2025.
Keywords: التناص، الملك لير، لير، المحاكاة الساخرة، نقد ما بعد الحداثة، التحليل الأسلوبي; Intertextuality; King Lear; Lear; Parody; Postmodern critique; Stylistic analysis.